Digital control of a novel single-phase three-port bidirectional converter to interface renewables and electric vehicles with the power grid - Monteiro, Vítor Duarte Fernandes (2017)
This paper presents the digital control of a novel single-phase three-port bidirectional (STB) converter used to interface renewables from solar photovoltaic (PV) panels and electric vehicles (EVs) with the power grid. Using an appropriated power theory, the STB converter can be used to exchange ener-gy between the PVs, the EVs and the power grid in four distinct modes: (1) The EV receives energy from the power grid (G2V - grid-to-vehicle operation mode) or delivers energy to the power grid (V2G - vehicle-to-grid operation mode); (2) All the energy produced by the PV panels is delivery to the power grid; (3) All the energy produced by the PV panels is delivery to the EV; (4) The EV can receive energy simultaneously from the PV panels and from the power grid (G2V). The currents of the power grid, PV panels and EV are con-trolled through independent predictive current control strategies, which ensure good power quality levels. This paper presents the architecture of the proposed STB converter and the detailed explanation of the digital implementation of the control algorithms, namely, the power theory and the predictive current control strategies. The control algorithms were validated through computational simula-tions and experimental results.